Portal vein thrombosis in cirrhosis: A literature review - Prakash, Swathi; Bies, Jared; Hassan, Mariam; Mares, Adriana; Didia, S. Claudia (Frontiers in Medicine, 2023)
Portal Vein Thrombosis (PVT), a common complication of advanced liver disease, is defined as an obstruction of the portal vein due to thrombus formation that can extend to the superior mesenteric and splenic veins. It was believed that PVT occurred predominantly due to prothrombotic potential. However, recent studies have shown that decreased blood flow related to portal hypertension appears to increase PVT risk as per Virchow’s triad. It is well known that there is a higher incidence of PVTs in cirrhosis with a higher MELD and Child Pugh score. The controversy for management of PVTs in cirrhotics lies in the individualized assessment of risks versus benefits of anticoagulation, since these patients have a complex hemostatic profile with both bleeding and procoagulant propensities. In this review, we will systematically compile the etiology, pathophysiology, clinical features, and management of portal vein thrombosis in cirrhosis.